African languages as compulsory courses in KwaZulu Natal: Illusory initiative or inspired intervention? - Turner, Noleen S. (Per Linguam : A Journal of Language Learning, 2012)
The point of departure in this article is the call by the Minister of Higher Education and Training in 2011 to introduce compulsory indigenous African language courses at tertiary institutions. The current language policy of the University of KwaZulu-Natal and the practicalities and difficulties of introducing the compulsory course at tertiary level is examined. The current language policy of the present South African Government and the negative attitudes of potential African language learners at schools and universities are discussed and a recommendation made for a possible way forward.